Maternal womb painting in high risk pregnant women hospitalized (Research, Society and Development, 2020)
Objective: To report the experience in performing the technique of maternal belly painting in high-risk pregnant women hospitalized, in the light of the Human Caring Theory. Method: This is the experience report of an intervention developed during practical classes of the Undergraduate Nursing course with high-risk pregnant women, admitted to the Gynecology and Obstetrics Clinic of a university hospital, which was analyzed in the light of Watson's Theory of Human Caring. Results: The painting of the mother's womb was carried out in five stages: encouraging the pregnant woman to describe the imaginary baby; maternal positioning and obstetric palpation; auscultation of cardiofetal beats; drawing of the imaginary baby described by the mother and elements related to pregnancy; and painting the drawings. Such activity made it possible to work on the positive emotions of pregnant women and strengthen the mother-baby bond. Nursing students allowed the development of obstetric palpation skills in a creative and innovative way, in addition to training aimed at humanistic care, which combines rationality and sensitivity. Conclusion: Maternal womb painting was presented as an innovative technique during practical nursing teaching activities, promoting transpersonal care to hospitalized high-risk pregnant women.